HDAC5 catalytic activity suppresses cardiomyocyte oxidative stress and NRF2 target gene expression - Hu, Tianjing; Schreiter, Friederike; Bagchi, Rushita A.; Tatman, Philip D.; Hannink, Mark; McKinsey, Timothy A. (The journal of biological chemistry, 2019)
Histone deacetylase 5 (HDAC5) and HDAC9 are class IIa HDACs that function as signal-responsive repressors of the epigenetic program for pathological cardiomyocyte hypertrophy. The conserved deacetylase domains of HDAC5 and HDAC9 are not required for inhibition of cardiac hypertrophy. Thus, the biological function of class IIa HDAC catalytic activity in the heart remains unknown. Here we demonstrate that catalytic activity of HDAC5, but not HDAC9, suppresses mitochondrial reactive oxygen species generation and subsequent induction of NF-E2-related factor 2 (NRF2)-dependent antioxidant gene expression in cardiomyocytes. Treatment of cardiomyocytes with TMP195 or TMP269, which are selective class IIa HDAC inhibitors, or shRNA-mediated knockdown of HDAC5 but not HDAC9 leads to stimulation of NRF2-mediated transcription in a reactive oxygen species-dependent manner. Conversely, ectopic expression of catalytically active HDAC5 decreases cardiomyocyte oxidative stress and represses NRF2 activation. These findings establish a role of the catalytic domain of HDAC5 in the control of cardiomyocyte redox homeostasis and define TMP195 and TMP269 as a novel class of NRF2 activators that function by suppressing the enzymatic activity of an epigenetic regulator.